Gerakan Kepemimpinan Dakwah di Era Digital - Oktavia Veby Ramawardhani; Egil Olimpia; Dea Firda Sari (DAWUH : Islamic Communication Journal, 2025)
This study aims to explain the movement of da'wah leadership in the digital era. According to Fiedler, a leader will not succeed or will fail if he only applies one style in carrying out his leadership, but the success of a leader in carrying out his leadership, if the leader is able to justify his various leadership styles with various situations faced in leading, or with a leadership style based on changes that occur in the organization. The research method uses literature studies, by analyzing 21 journals as primary data. Data analysis with several stages, the first stage determines the theme, the second stage selects journal articles that are relevant to the theme and in accordance with the deadline of the last 4 years, the third stage is the review process of 7 journal articles, the fourth stage is categorization and the fifth stage is drawing conclusions. The results of the study show that the importance of da'wah in the field of Islamic leadership is to form leaders who are based on values such as justice, trustworthiness, and honesty in accordance with Islamic teachings. The biggest challenge in this da'wah is conveying the message to the millennial generation who tend to be more dependent on technology. One effective method to achieve this is through social media, especially podcasts, which are popular among them. With an engaging, flexible, and easily accessible format, podcasts are the perfect medium to deliver Islamic leadership messages in a persuasive and well-received manner to the audience